Chemical soil and leaf properties in yellow passion fruit cultivation with organic fertilization - Almeida, Waldiane Araújo de; Araújo Neto, Sebastião Elviro de; Uchôa, Thays Lemos; Souza, Luís Gustavo de Souza e; da Silva, Nilciléia Mendes; Ferreira, Regina Lúcia Felix; Tomio, Denis Borges (Comunicata Scientiae, 2020)
The yellow passion fruit presents a high nutritional demand, and successive cultivations in the same area lead the soil to nutritional exhaustion, creating the need for restitution through fertilizers. In the context of organic managements, alternatives must be sought, which, besides improving soil fertility, can increase the contents of soil organic matter. Therefore, this work aimed to evaluate the effect of organic basal fertilization in passion fruit cultivation on the chemical properties of the soil and nutrient contents of the plant. Two experiments were performed in two rural properties, with soils presenting sandy-loam and clay-loam texture. The experimental design was in randomized blocks (RBD), with 5 treatments and 4 blocks. The treatments consisted of the application of organic compost in different planting hole diameters: 0.4 m; 0.8 m; 1.2 m; 1.6 m, and 2.0 m, and their respective volumes of organic compost: 0.0007 m³; 0.03 m³; 0.06 m³, 0.10 m³; 0.16 m³. The chemical characteristics of the soil and the foliar content of nutrients were evaluated. Soil texture interferes with the effects of organic fertilization. Regardless of the texture, fertilization increases the contents of organic matter and P in the soil. The successive organic cultivation in a sandy-loam soil increases the content of P and provides higher foliar contents of N, P, Ca, Mg, S, B, Cu, Fe, Zn, and Na.